Ginsenoside Rg1 Delays Chronological Aging in a Yeast Model via CDC19- and SDH2-Mediated Cellular Metabolism - Siming Wang; Juhui Qiao; Chunyan Jiang; Daian Pan; Shiting Yu; Jingjing Chen; Shichao Liu; Peiguang Zhang; Daqing Zhao; Meichen Liu (Antioxidants, 2023)
Ginsenosides, active substances in Panax ginseng C. A. Meyer (ginseng), extend lifespan in multiple species, ameliorate age-associated damage, and limit functional decline in multiple tissues. However, their active components and their molecular mechanisms are largely unknown. Here, ginsenoside Rg1 (Rg1) promoted longevity in Saccharomyces cerevisiae. Treatment with Rg1 decreased aging-mediated surface wrinkling, enhanced stress resistance, decreased reactive oxygen species’ production and apoptosis, improved antioxidant enzyme activity, and decreased the aging rate. Proteomic analysis indicated that Rg1 delays S. cerevisiae senescence by regulating metabolic homeostasis. Protein–protein interaction networks based on differential protein expression indicated that CDC19, a homologue of pyruvate kinase, and SDH2, the succinate dehydrogenase iron–sulfur protein subunit, might be the effector proteins involved in the regulation by Rg1. Further experiments confirmed that Rg1 improved specific parameters of mitochondrial bioenergetics and core enzymes in the glycolytic pathway. Mutant strains were constructed that demonstrated the relationships between metabolic homeostasis and the predicted target proteins of Rg1. Rg1 could be used in new treatments for slowing the aging process. Our results also provide a useful dataset for further investigations of the mechanisms of ginseng in aging.